The social framework : an introduction to economics - Hicks, John (Oxford : Clarendon Press, 1971)
This book begins with the theory of demand and supply. It explains social framework policies in economic theory.
Includes index
Includes bibliographical references.
asm; 01/07/19
Loans
Keywords: Economics